2015
DOI: 10.1590/1984-70332015v15n3c35
|View full text |Cite
|
Sign up to set email alerts
|

URS Brava - a new oat cultivar with partial resistance to crown rust

Abstract: -

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…This response is supported by previous research that found at low disease intensity with resistant cultivars an application of pyraclostrobin did not improve test weight (May et al., 2014). It should be remembered that at high levels of disease severity an effective fungicide application will protect test weight and reduce any reduction in test weight (Federizzi et al., 2015; May et al., 2014; van Niekerk et al., 2001).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This response is supported by previous research that found at low disease intensity with resistant cultivars an application of pyraclostrobin did not improve test weight (May et al., 2014). It should be remembered that at high levels of disease severity an effective fungicide application will protect test weight and reduce any reduction in test weight (Federizzi et al., 2015; May et al., 2014; van Niekerk et al., 2001).…”
Section: Resultsmentioning
confidence: 99%
“…When the genetic resistance is overcome or not incorporated into an oat cultivar a fungicide application can protect grain yield and quality. Fungicide applications have been used in various environments around the world to reduce grain yield loss from crown rust (Dietz, Schierenbeck, & Simón, 2019; Federizzi, Pacheco, & Nava, 2015; van Niekerk, Pretorius, & Boshoff, 2001). On the northern portion of the North American Great Plain, May et al.…”
Section: Introductionmentioning
confidence: 99%
“…URS Brava and URS Altiva were released as cultivars in 2014 and 2015, respectively, with phenotypic traits of race-non-specific resistance to crown rust (FEDERIZZI et al, 2015;NAVA et al, 2016). URS Altiva was more susceptible when compared to URS Brava and URS 21.…”
Section: Discussionmentioning
confidence: 99%
“…The no-tillage cropping system, on subtropical environments, allows cultivating the oat crop during the winter-spring time and, after its harvest, it is possible to establish the soybean crop (Federizzi et al, 2015). However the oat crop grain yield is decreasing during recent years (Federizzi et al, 2015), in part due to weed competition (Lemerle et al, 1995;Begna et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The no-tillage cropping system, on subtropical environments, allows cultivating the oat crop during the winter-spring time and, after its harvest, it is possible to establish the soybean crop (Federizzi et al, 2015). However the oat crop grain yield is decreasing during recent years (Federizzi et al, 2015), in part due to weed competition (Lemerle et al, 1995;Begna et al, 2011). For instance, Lolium rigidum competition reduces oat grain yield by 14% (Lemerle et al, 1995), whereas Chenopodium album interference decreases this crop grain yield by 10% (Begna et al, 2011).…”
Section: Introductionmentioning
confidence: 99%